The Innovation Paradox of Registration Reform: Inefficient Investment Mediation Effects and Heterogeneous Firm Responses - He, Xingyuan; Xie , Shushu; Li, Jie (Transformations In Business & Economics, 2025)
Registration system reform aims to optimize resource allocation and stimulate market dynamics. Many countries have adopted it as a key institutional innovation in their capital markets. However, whether such reform effectively promotes corporate innovation—especially across different enterprise types—remains unclear. To explore the innovation paradox of registration reform, drawing on information asymmetry and investor behavior theories, and using data from the Chinese A-share Growth Enterprise Market (GEM) and Main Board firms covering the period from 2018 to 2022, the impact of the reform, the underlying mechanisms, and the heterogeneous effects on innovation were analyzed with a difference-in-differences (DID) approach. Results show that the registration system reform does not promote corporate innovation as expected. Although the reform has led to an increase in overall enterprise investment, much of this additional investment is inefficient. As a result, the overall innovation capacity of firms has declined. This finding confirms that inefficient investment acts as a mediating factor through which reform weakens corporate innovation. Further analysis reveals significant differences in the impact of the reform. The negative effects are most pronounced for non-manufacturing enterprises, firms located in the eastern region, and companies with low price‒earnings ratios. For other firm types, the impact is not significant. This study highlights the unintended consequences of reforming the registration system for corporate innovation, particularly when investment efficiency does not improve. The conclusions obtained from this study contribute to the theoretical understanding of innovation and offer practical insights for optimizing future reform policies.
Keywords: registration reform; enterprise innovation; inefficient investment